2019
DOI: 10.7287/peerj.preprints.27871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of complementary sex determination in Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae)

Abstract: Over 60 species in Hymenoptera have been reported to possess a complementary sex determination (CSD) system. Under CSD, sex is determined by allelic complementation at one or several sex loci. But this mechanism is still uninvestigated in parasitoid wasp Trichogramma dendrolimi, one of the most important biocontrol agents widely used against Lepidopteran pests. We tested CSD in this species by conducting ten consecutive generations of inbreeding, to monitor both direct evidence (diploid male production) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Wolbachia species, which are naturally occurring endosymbiotic bacteria found inside the cells of arthropods and filarial nematodes, can manipulate the host reproduction system [82] and are generally known as potential environmentally friendly biopesticides for the control of disease vectors and pests [154]. Recent studies found that Wolbachia species infect approximately 40% of terrestrial arthropod species, such as Lepidoptera, Hymenoptera, and Diptera species [155,156]. Cytoplasmic incompatibility (CI) is one of the most common phenotypes of reproductive manipulation in Wolbachia [157].…”
Section: Potential Application Of Gut Symbionts In Controlling Lepido...mentioning
confidence: 99%
“…Wolbachia species, which are naturally occurring endosymbiotic bacteria found inside the cells of arthropods and filarial nematodes, can manipulate the host reproduction system [82] and are generally known as potential environmentally friendly biopesticides for the control of disease vectors and pests [154]. Recent studies found that Wolbachia species infect approximately 40% of terrestrial arthropod species, such as Lepidoptera, Hymenoptera, and Diptera species [155,156]. Cytoplasmic incompatibility (CI) is one of the most common phenotypes of reproductive manipulation in Wolbachia [157].…”
Section: Potential Application Of Gut Symbionts In Controlling Lepido...mentioning
confidence: 99%
“…The progeny sex ratio further depends on the viability of diploid males, the fertilization rate and the number of sex determination loci (Table 1 ). Therefore, a protocol of multiple inbreeding generations must be used to assess ml‐CSD (Cook, 1993a ; Beukeboom et al ., 2000 ; Ma et al ., 2013 ; Paladino et al ., 2015 ; Liu et al ., 2019 ).…”
Section: Methodsmentioning
confidence: 99%